Diagnosing and managing patients with heart failure with preserved ejection fraction: a consensus survey - Christi Deaton; Robin Fox; Ian Wellwood; Carolyn Chew-Graham; Katherine Brown; Sharon Dixon; Thomas Blakeman; Alistair Brown; Julie Smith; Nick Thomas; Adam Jones; Basilio Hernandez-Diaz; et al. (BMJ Open)
Aim As heart failure (HF) with preserved ejection fraction (HFpEF) prevalence increases, it remains frequently underdiagnosed and poorly managed. Recent positive pharmacological trials have increased interest in HFpEF but challenges of diagnosis and management remain. The survey aim was to examine consensus between primary and secondary care providers regarding HFpEF diagnosis and management.Methods As part of a larger programme of work, survey questions were developed in an online format and piloted with healthcare providers (HCPs). The survey link was distributed via professional networks and social media. Analysis included frequencies of responses, comparison by main professional groups and thematic analysis free-text responses. A virtual workshop of HCPs was conducted to discuss and refine survey findings.Results HCPs (n=66) across the UK participated: 19 general practitioners (GPs), 20 HF specialist nurses (HFSN), 17 cardiologists and 10 others. Consensus was high (92%) that diagnosing the type of HF was very important and most favoured inclusion of HFpEF in Quality Outcome Framework indicators. No clear consensus was reached that ongoing management should be in primary care (47.5% of GPs, 35% of HFSN and 31.3% of cardiologists ‘somewhat agreed’). Opinions differed between GPs (52.3)% and specialists (HFSN 80% and cardiologists 81.3%) for practice nurses to be upskilled and assume HFpEF management. No HCPs reported any level of disagreement for HFSN management of HFpEF. Free-text comments highlighted resource barriers to HFpEF diagnosis and management and confirmed the need to develop better HFpEF services.Conclusions Consensus was reached regarding importance of diagnosing HFpEF, but agreement on methods and responsibilities for diagnosis and management varied. Free-text comments identified HCPs concerns related to overwhelmed primary and secondary care services and lack of sufficient resources to meet existing patient demands. Creation of collaborative care pathways is needed to support the increasing number of older patients with HFpEF.Trial registration number ClinicalTrials. gov (reference number: NCT03617848).